Commentary on the Gospel of St John ; v.1 - Hengstenberg, Ernst Wilhelm, 1802-1869 (Minneapolis, MN Klck and Klock)
Contents : v. 1 : John I. 1- X.42. Includes bibliographcial references.
Originally published by T. and T. Clark, Edinburgh, Scotland, 1865. This reprint : 1980
Keywords: Bible. N.T. John I-X -- commentaries